Homicídios na fronteira internacional entre o Brasil e o Paraguai: considerações sobre Foz do Iguaçu e a Região Metropolitana da Cidade do Leste - Kleinschmitt, Sandra Cristiana (2012)
The goal of this thesis was to investigate the profile of homicides on the border between Brazil and Paraguay, in order to propose some hypotheses about the high rates of homicide in Foz do Iguacu, Parana. The technical procedure for the study was to research on police's pages of the newspapers "A Gazeta do Iguaçu" Foz do Iguaçu and "Diary Vanguardia" Ciudad del Leste. The period researched was between August 5, 2010 to 05 August 2011. The collected data were treated quantitatively. The results indicate that victims in Foz do Iguaçu and in the metropolitan area of Ciudad del Este (RMCDL) were male and predominantly young people and adolescents. The most widely used weapon for to consummation of the crime are fire guns. The crimes occurred on public roads, especially at night. Considering the high amount of bullets and the "modus operandi" of the killings in Foz do Iguacu, there are strong signs of summary execution. For RMCDL, the data reveal a different situation, since the motivations presented show evidences of intersubjective homicides and robbery. In this context, among the hypotheses in the research, such as social inequality, the slowness of the justice system and corruption of the state, it is clear that deaths from summary executions merit special attention. Not discarding the specific characteristics of the place in focus (other associated conditions) such as the situation along the border with Paraguay and high cash circulation.